The Fallacies of Deliberate Action: Examining Intent within the Indonesian Criminal Justice Framework - Waldo, Risky; Budianto, Azis (Greenation Publisher & Yayasan Global Resarch National, 2025)
This study critically examines the conceptualization, interpretation, and application of intent (mens rea) within Indonesia's criminal justice system, identifying significant fallacies that undermine accurate assessment of mental states in criminal proceedings. Through qualitative analysis of judicial decisions, legal frameworks, and scholarly discourse, the research reveals conceptual incongruities in how intent is defined across different categories of crimes and inconsistently applied in courtroom contexts. The findings demonstrate that Indonesian courts predominantly rely on behavioral indicators as proxies for internal mental states, often overlooking the complex psychological processes that constitute genuine intent. Procedural and evidentiary challenges further complicate intent assessment, with psychological evaluations rarely utilized despite their relevance to mental state determination. Sociocultural and institutional factors—including linguistic variations, cultural diversity, and institutional pressures—introduce additional complexity to intent interpretation, creating potential for systematic biases that do not align with statutory definitions or psychological realities. The study proposes comprehensive reforms to address these fallacies, including revised legal frameworks that incorporate contemporary psychological insights, standardized procedures for psychological evaluation in criminal proceedings, enhanced interdisciplinary training for legal actors, and culturally responsive approaches that recognize diverse conceptualizations of intent while maintaining legal consistency. These reforms would contribute to more accurate assessments of criminal intent and enhance justice outcomes in Indonesia's criminal proceedings.